The Logics of and Strategies to Enhance Generalization of Mixed Methods Research Findings - Ahtisham Younas; Angela Durante (Methodology, 2023)
Generalization of research findings is a cognizant action entailing careful examination and interpretation of findings drawn from specific samples and extrapolation of those findings to other diverse populations and settings. Approaches to generalization in qualitative and quantitative research have been discussed in the literature. However, there is limited discussion about the nature of generalization and strategies for achieving plausible generalization in mixed methods research. The purpose of this paper is to explore the logics of generalization in mixed methods and offer strategies to enhance generalization in mixed methods research. Three strategies namely, multilevel integration, comprehensive description of mixed methods and findings, and generating strong and plausible inferences and metainferences can enhance the extent to which findings of mixed methods studies can be translated outside of their own original context. These strategies may allow researchers to effectively combine qualitative and quantitative methodologies and generate findings for use in diverse contexts and settings.